Comparative oncology approach to drug repurposing in osteosarcoma. - Alejandro Parrales (PLoS ONE, 2018)
BACKGROUND:Osteosarcoma is an orphan disease for which little improvement in survival has been made since the late 1980s. New drug discovery for orphan diseases is limited by the cost and time it takes to develop new drugs. Repurposing already approved FDA-drugs can help overcome this limitation. Another limitation of cancer drug discovery is the lack of preclinical models that accurately recapitulate what occurs in humans. For OS using dogs as a model can minimize this limitation as OS in canines develops spontaneously, is locally invasive and metastasizes to the lungs as it does in humans. METHODS:In our present work we used high-throughput screens to identify drugs from a library of 2,286 FDA-approved drugs that demonstrated selective growth inhibition against both human and canine OS cell lines. The identified lead compound was then tested for synergy with 7 other drugs that have demonstrated activity against OS. These results were confirmed with in vitro assays and an in vivo murine model of OS. RESULTS:We identified 13 drugs that demonstrated selective growth inhibition against both human and canine OS cell lines. Auranofin was selected for further in vitro combination drug screens. Auranofin showed synergistic effects with vorinostat and rapamycin on OS viability and apoptosis induction. Auranofin demonstrated single-agent growth inhibition in both human and canine OS xenografts, and cooperative growth inhibition was observed in combination with rapamycin or vorinostat. There was a significant decrease in Ki67-positive cells and an increase in cleaved caspase-3 levels in tumor tissues treated with a combination of auranofin and vorinostat or rapamycin. CONCLUSIONS:Auranofin, alone or in combination with rapamycin or vorinostat, may be useful new treatment strategies for OS. Future studies may evaluate the efficacy of auranofin in dogs with OS as a prelude to human clinical evaluation.